Plasma protein profiling analysis in patients with atrial fibrillation before and after three different ablation techniques - Lin, Menglu; Bao, Yangyang; Du, Zunhui; Zhou, Yanting; Zhang, Ning; Lin, Changjian; Xie, Yinyin; Zhang, Ruihong; Li, Qiheng; Quan, Jinwei; Zhu, Tingfang; Xie, Yuan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There are controversies on the pathophysiological alteration in atrial fibrillation patients undergoing pulmonary vein isolation using different energy sources. Objectives We evaluated the changes of plasma proteins in acute phase post ablation in patients receiving cryoballoon ablation, radiofrequency balloon ablation or radiofrequency ablation. Methods Blood samples from 8 healthy controls and 24 atrial fibrillation patients were taken on the day of admission, day 1 and day 2 post ablation and analyzed by the Olink Proximity Extension Assay. Proteins were identified and performed with enrichment analysis. Protein-protein interaction network and module analysis were conducted using Cytoscape. Results Out of 181 proteins, 42 proteins in cryoballoon group, 46 proteins in radiofrequency balloon group and 43 proteins in radiofrequency group significantly changed after ablation. Most of proteins altered significantly on the first day post ablation. Altered proteins were mainly involved in cytokine-cytokine receptor interaction. Both balloon-based ablations showed similar shift towards enhancing cell communication and regulation of signaling while inhibiting neutrophil chemotaxis. However, radiofrequency ablation presented a different trend. Seed proteins including osteopontin, interlukin-6, interlukin-10, C-C motif ligand 8 and matrix metalloproteinase-1 were identified. More significant proteins associated with hemorrhage and coagulation were selected in balloon-based ablations by machine-learning. Conclusions Plasma protein response after three different ablations in atrial fibrillation patients mainly occurred at the first day. Radiofrequency balloon ablation shared similar alteration in protein profile as cryoballoon ablation comparing with radiofrequency ablation, suggesting lesion size rather than energy source is the determinant in pathophysiological responses to the ablation.